2021
DOI: 10.33603/jpa.v4i2.5886
|View full text |Cite
|
Sign up to set email alerts
|

Persepsi Konsumen Terhadap Keberadaan Coffee Shop Dan Barista Pada Era Pemasaran Kopi Ke Tiga

Abstract: Dewasa ini, pemasaran kopi dunia memasuki era ke tiga yang ditandai banyak munculnya kedai kopi modern (coffee shop). Selain itu muncul keinginan konsumen untuk lebih mengenal kopi dari origin hingga sampai kepada tahap akhir, mengkonsumsi minuman kopi yang nikmat sehingga melahirkan profesi barista. Oleh karenanya konsumen yang berada pada masa transisi akan dihadapkan pada masalah persepsi terhadap fenomena tersebut dalam kaitannya dengan keberlanjutan usaha. Penelitian ini bertujuan untuk mengetahui perseps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…The results showed that the effect of product (X3) on business sustainability (Y) or X3→Y is significant (real) with a standardised regression coefficient value of 0.8 and is positive, meaning that if X3 is increased by 100% it will increase Y by 80%. The nature of the effect is inelastic, meaning that the proportion of changes in X3 is greater than the proportion of changes in Y (Wachdijono & Yahya, 2021). Products have a positive effect on the sustainability of coffee shops in the lowlands of Tangerang City, indicating that consumers are very concerned about the existence of coffee beverage products, meaning that if there is a change in product conditions, it…”
Section: The Influence Of Product (X3) On Coffee Shop Business Sustai...mentioning
confidence: 99%
“…The results showed that the effect of product (X3) on business sustainability (Y) or X3→Y is significant (real) with a standardised regression coefficient value of 0.8 and is positive, meaning that if X3 is increased by 100% it will increase Y by 80%. The nature of the effect is inelastic, meaning that the proportion of changes in X3 is greater than the proportion of changes in Y (Wachdijono & Yahya, 2021). Products have a positive effect on the sustainability of coffee shops in the lowlands of Tangerang City, indicating that consumers are very concerned about the existence of coffee beverage products, meaning that if there is a change in product conditions, it…”
Section: The Influence Of Product (X3) On Coffee Shop Business Sustai...mentioning
confidence: 99%
“…(NW Some previous research results related to the matters above include: 1) Haristianti et al (2021) and Farasa & Kusuma (2015) explained that consumers feel at home in coffee shops for a long time because they feel comfortable with the atmosphere of the shop; 2) Indasari & Bachri (2021) and Purnomo (2017) summarize the store atmosphere influence purchasing decisions; 3) Medikana et al, (2018) and Pramatatya et al, (2004) concluded that the store atmosphere influence on purchases; 4) Afriyanti and Rasmikayati (2018) explained that consumers visit coffee shops to enjoy the atmosphere; 5) Spence et al, (2014) emphasized that the store atmosphere has a strong influence on consumer behavior in purchasing (Spence et al, 2014); 6) Aprilia & Suryani (2020), Pratiwi et al, (2022) and Ayuningtyas et al, (2022) summarize the store atmosphere has a natural effect on consumer satisfaction. Apart from that, several other research results add that the barista variable can increase brand values, including the image of the store atmosphere (Dhifan & Yuningsih, 2022), consumer perceptions of the coffee shop barista variable are at an optimistic level in supporting business development (Wachdijono & Yahya, 2021), Barista interpersonal communication variables influence consumer satisfaction (Pambayun & Soedarsono, 2019) and the barista competency variable in the very high category so that it can support the store atmosphere which is convenient for consumers (Alvarizy & Deliana, 2021). However, there are differences with the research results of Utomo (2023), who shows that the barista service at the Starbucks Coffee Shop still needs to be higher.…”
Section: Introductionmentioning
confidence: 99%
“…The existence of the coffee products industry which continues to grow has resulted in a large demand for coffee by the industry. The industry has criteria for the best quality coffee raw materials to produce products that consumers like (Wachdijono & Yahya, 2021). Consumers have a preference for coffee products with a rich, fresh aroma and a balanced taste (Andika, Yusriana, & Rasdiansyah, 2023).…”
Section: Introductionmentioning
confidence: 99%